Effect of Vanillic Acid on Nerve Conduction Velocity in Chronic Constriction Injury Model of Neuropathy - Pawar, Shubhangi; Khairnar, Shubham; Patil, Vinod; Bhambar, Rajendra (Indian Journal of Pharmaceutical Education and Research, 2020)
Background: Neuropathic Pain (NP) is less or symptomatically managed by presently available therapeutics. Therefore developing more effective drugs with minimum adverse effects is essential. Vanillic acid is phenolic secondary plant metabolite. Extensive research regarding phenolic acids with antioxidant, free radical scavenging and neuroprotective roles have been published. Objectives: The aim of this undertaken study was to evaluate the efficacy of vanillic acid (V.A.) to improve nerve conduction velocity in neuropathic pain induced by CCI (chronic constriction injury) and to evaluate its antioxidant potential. Methods: Rats were divided into 7 groups (n=6), as negative control, positive control (CCI), sham control, CCI+gabapentin (300 mg/kg, p.o.), V.A. (25 mg/kg, p.o.), V.A. (50 mg/kg, p.o.) and V.A. (100 mg/kg, p.o.). After surgery oxytetracycline (25 mg/kg, i.m.) was administered in animals to avoid any infection. Vanillic acid and gabapentin administered post-surgery from day 4th till 28th day. Velocity of nerve conduction and antioxidant and histopathological studies were conducted on 28th day. Results: Repeated oral administration of vanillic acid (50 mg/kg, 100 mg/kg) significantly improved MNCV. V.A. showed antioxidant property by significantly elevating level of GSH and also reversed histopathological changes induced by CCI. Conclusion: This study has suggested antioxidant and neuroprotective effect of vanillic acid in CCI induced peripheral neuropathy.
Keywords: CCI; MNCV; Neuropathy; Gabapentin; Vanillic acid